Empreendedorismo sustentável: causas da mortalidade das micro e pequenas empresas no município de Guarapuava-PR no período de 2006 a 2010 - Sansana, José Carlos (2013)
The present study aims to know the causes of micro and small enterprises – MPEs bankruptcy in Guarapuava –PR, from 2006 to 2010. In the research, it was raised the number of MPEs that were created and closed during that period in the commercial, industrial and services sectors; besides, six representatives from linked institutions and of promotion for the MPEs, understanding that the identification of the probable causes of the extinction of those enterprises can contribute for the arising of new ventures in better conditions to enterprising success. The methodology approach used was the qualitative research, where the respondents were asked to answer several questions about the economical, social and environmental variables and the performance of the extinct enterprises in the different issues of those variables. The obtained results evidenced a minor or very small contribution of the social and environmental variables and a very big one of the economical variable as causes for the enterprises bankruptcy, due to the little knowledge of business management, with failures and omissions in all their functional areas. It was possible to conclude as well that, even going through problems of all sorts, an obstacle of cultural nature occurred in the MEPs that closed their doors: they did not seek for assistance, orientation or consulting with the specialized institutions.